The Effect of Diesel Exhaust Exposure on Railroad Worker Health and Mortality: A Survey of Somewhat Competing Evidence - Tannen, Michael (Archives of Business Research, 2021)
Hazardous work conditions expose employees to health and safety risks, and employers to potentially higher expenses including the possibility of a prolonged series of expensive litigation. Indeed, recognition of this in individual and organized (collective) bargaining over higher pay and health benefit coverage, and of course, government regulation involving improved safety measures and equipment design is common. It is easier for all to deal with such risks when they are recognized, and the extent of that risk known. Often, though, risks may appear uncertain, with contradictory evidence supporting opposing views. Such is the case for the exposure of railroad workers to diesel exhaust, a subject that has been investigated for decades with considerable disagreement. This paper contains a focused survey of published studies in the past thirty-five years using observational data and epidemiology (laboratory studies on animals) to review the extent to which disagreement has or not been abated.